Implementasi Program Madrasah Ramah Anak Di Min Kota Blitar - Kharismatul Mufidah, Intan; Uyun, Fitratul (IBTIDA', 2023)
This research aims to analyze the implementation of the Child-Friendly Madrasah Program (MRA) at Madrasah Ibtidaiyah Negeri (MIN) Blitar City. MRA is an educational approach that focuses on creating a learning environment that is safe, and inclusive and supports children's holistic development. Against the background of the need for education responsive to children's rights, this research focuses on how MIN Blitar City accepts and implements the MRA concept. This research uses a descriptive qualitative approach. Data was collected through interviews and direct observation. The results of this research show that MIN Blitar City has made various efforts to implement the Child-Friendly Madrasah (MRA) program. Aspects include physical security, student involvement in decision-making, paying attention to student's special needs, and integrating human values in learning to implement Child-Friendly Madrasas (MRA). However, challenges include limited infrastructure and uneven understanding of the Child-Friendly Madrasah (MRA) concept among all staff. The implication of this research is that MIN Kota Blitar can continue to strengthen the implementation of the Child-Friendly Madrasah Program by providing further training to staff, involving more students in the decision-making process, and expanding parent involvement in supporting this approach. It is hoped that this research can contribute to an understanding of the development of education that is more inclusive and responsive to the needs of children in the madrasa environment.